The Role of Saudi Arabia’s Copyright Law in Governing the Modern Video Game Landscape (The International Journal for Scientific Research, 2024)
Saudi Arabia’s billion-dollar gaming industry is experiencing a rapid transformation marked by exponential growth and substantial investment. The Kingdom is the 19th biggest gaming market worldwide, with an investment of $6.4 billion to support the industry’s development. The exponential growth and substantial investment in the Kingdom’s gaming industry emphasize the significance of understanding the role of its Intellectual Property law, particularly copyright, in administering this dynamic landscape. Understanding this role will help to demonstrate the Kingdom’s dedication to encouraging the growth and development of the video game industry. As part of its 2030 Vision, Saudi Arabia’s Public Investment Fund (PIF) has entered the gaming sector by establishing Savvy Gaming Group, which invested $1.05 billion to acquire FACEIT and ESL, forming the ESL FACEIT Group. This article examines the intersection of video games and Intellectual Property law, focusing on copyright to explore how the Kingdom’s current copyright framework accommodates the distinctive elements of the video gaming industry and addresses the legal ambiguities that potentially undermine the industry’s copyright protection and overall growth and development. The article analyses the levels of existing copyright protection and legal ambiguities in the Kingdom of Saudi Arabia. Consequently, this article proposes a copyright system tailored to the video gaming industry to address the Kingdom’s specific challenges in this domain. Conclusively, it contends that existing copyright laws do not adequately accommodate Saudi Arabia’s dynamic video gaming industry. It advocates for discussions on a new regime that caters to the industry’s unique aspects and safeguards the interests of publishers and creators in the emerging gaming sector.
Keywords: Video Games; Saudi Arabia; Saudi Copyrights Act; IP Protection